A distributed data secure transmission scheme in wireless sensor network. (April 2017) - Liang, Wei; Huang, Yin; Xu, Jianbo; Xie, Songyou
Sensor nodes around monitoring area have various distances to the target node. Therefore, it is difficult to ensure security of broadcasting data transferred from a single wireless sensor node to base station. Multi-hop transmission of data between sensor nodes wastes network resource. In this case, a distributed data secure transmission scheme is proposed in a wireless sensor network. Data transmission is classified into two stages: constructing a collection of receiving nodes and selecting a unique forwarding node from this collection. These are implemented using analysis of relative movement distance between nodes and transfer time competitive mechanism. Besides, we have assumed a network model for distributed data secure transmission to improve efficiency of data transfer. This design includes secure model of node competition, data perception model, and anti-resistance model. Moreover, the security of competition transfer for nodes in wireless sensor network is evaluated. Finally, simulation proves that the proposed scheme has good performance in security and stability compared to similar schemes.